Cobertura arbórea y herbácea en pasturas naturalizadas de fincas ganaderas del Trópico Seco de Nicaragua - Velásquez Vélez, Raúl; Mora Delgado, Jairo (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary In pastures with very diverse botanical composition, as is the case of naturalized pastures in Muy Muy (Nicaragua), it is important to know which species are present in the pasture, because they constitutes a part of the diet for the cattle. That floristic composition change in the pastures managed under different grazing conditions. We evaluated cover, floristic composition and type of the arboreal and herbaceous vegetation under two landscape condition (undulating lands and riverbanks), and two animal management systems, during the dry and wet seasons. Three treatments studied were: "vega" (milking cows grazing in the riverbanks), "leche" and "horro" (milking and dry cows, respectively, grazing in undulating lands), each with eight paddocks as replicates. A simple random sampling was done of treatments in 24 units (paddocks). Inventory of species was carried out adapting the methodology described by Jansson used to study cows’ selectivity at different spatial scales. Species diversity was greater in the undulating lands than in the riverbanks. In the latter, Panicum maximum grass was the most common species. Botanic composition of herbaceous vegetation in vegas was different to of undulating lands, in dry season (p < 0.01) and wet season. The most frequent specie on the riverbanks was Asia grass (Panicum maximum).